Role of parental divorce and discord in the intergenerational transmission of alcohol use disorder. (1st May 2022) - Salvatore, Jessica E.; Aggen, Steven H.; Kendler, Kenneth S.
Abstract: Background: Alcohol use disorder (AUD) has a strong familial component, and is associated with divorce and relationship discord. The purpose of this study was to test whether exposure to parental divorce and parental relationship discord contributes to the intergenerational transmission of AUD. Methods: The sample included N = 9005 adult twins (43% female) from the Virginia Adult Twin Study of Psychiatric and Substance Use Disorders. Participant AUD diagnoses were derived from structured clinical interviews based on DSM-IV alcohol dependence. Participants also reported on parental divorce and parental AUD. In addition, direct psychiatric interview data and measures of relationship discord were available for a subsample of parents of female-female twin pairs (855 mothers, 617 fathers). Indirect effects models were fit and tested using a robust maximum likelihood estimator with Monte Carlo integration. Results: Path and structural equation modeling results provided strong support for the intergenerational transmission of AUD, and indicated that parental AUD had indirect effects on offspring AUD through exposure to parental divorce and parental relationship discord. Effects were consistent across males and females. Conclusions: In a population-based adult twin sample, exposure to parental divorce and relationship discord appears to be important for understanding the intergenerational transmission of AUD. These effects are broadly consistent with the idea of genetic nurturance, whereby parents transmit genetic risk for alcohol use disorder to their children indirectly via heritable aspects of the home environment. Ultimately, this etiological information could bolster engagement with skills-based therapeutic efforts used in substance-related preventive interventions for divorced or distressed families. Graphical Abstract: ga1 Highlights: Alcohol use disorder is transmitted across generations in families. Family stressors, like divorce and relationship discord, are more common in families where a parent has an alcohol use disorder. Parental divorce and relationship discord contribute to the intergenerational transmission of alcohol use disorder.